2021
DOI: 10.29289/2594539420200068
|View full text |Cite
|
Sign up to set email alerts
|

Patient navigation: fighting for the rights of breast cancer patients in Brazil

Abstract: Introduction: The content of this article deals with the experience of the navigation program for patients in a breast cancer diagnosis center of the State Health Department of Rio de Janeiro. The objective was to show how the patient navigation program can allow the proper application of the 60-day Law, being a topic of interest for the planning and evaluation of actions to control this cancer in Brazil. Methodology: The patient navigator accompanied women from the Unified Health System (Sistema Único de Saúd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In our study, it was found that the mean time between the first visit to the mastologist and the histological diagnosis of BC was 63.2 days, and the mean time between histological diagnosis and the beginning of treatment was 39.6 days. In a recent study conducted by Gioia et al in Rio de Janeiro, Brazil, the mean time to start treatment was 39 days 35 . It can be perceived in our study that the beginning of the treatment is within what is recommended by law; however, as observed in other studies, a delay is identified concerning the time of diagnosis of BC, with reports of the average delay reaching 142.5 days in other Brazilian surveys 36 .…”
Section: Discussionmentioning
confidence: 97%
“…In our study, it was found that the mean time between the first visit to the mastologist and the histological diagnosis of BC was 63.2 days, and the mean time between histological diagnosis and the beginning of treatment was 39.6 days. In a recent study conducted by Gioia et al in Rio de Janeiro, Brazil, the mean time to start treatment was 39 days 35 . It can be perceived in our study that the beginning of the treatment is within what is recommended by law; however, as observed in other studies, a delay is identified concerning the time of diagnosis of BC, with reports of the average delay reaching 142.5 days in other Brazilian surveys 36 .…”
Section: Discussionmentioning
confidence: 97%
“…It aimed to help women diagnosed with BC in the public system to start treatment at a specialized center within 60 days of diagnosis. As part of the BC PNP program, a trained social worker facilitated patients' navigation through the health care system by providing services such as diagnostic consultation scheduling, follow-up assistance, referral facilitation, and coordinating communication between patients and healthcare professionals 6,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The central pillar is recognizing the importance of understanding the patient's experience to advance towards patientcentered care 8 . The problem of accessing healthcare services requires better solutions and for populations in areas where healthcare access is fragmented, and healthcare systems can be fragile and underfunded 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation